STRATEGI PENGEMBANGAN KURIKULUM BERBASIS KOMPETENSI DUDI UNTUK SMK - Widiyanto, Widiyanto (Fakultas Ekonomi, Universitas Negeri Semarang, 2010)
Complaints of workplaces about graduatesâ competencies of vocational schools were still going on. Workplaces need competent and efficient workers; therefore, vocational schools have to fulfill these needs. The graduatesâ competencies are based on the curriculum, so the vocational schools must develop a strategy to improve the curriculum for achieving the competency needs of workplaces. The objective of this research is to provide the strategy in developing the curriculum based on workplace competencies. This study used qualitative approach and interaction methods to construct a strategy to develop the curriculum based on workplace competency. The conclusions are, first vocational schools need to identify the need of workplace competency, and secondly, those competencies identified are needed to make the competencies strategy based on workplace. The implication of this research supports Spencer & Spencer (1993) and Judissuseno (2008) theories.